2021
DOI: 10.5888/pcd18.200531
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Preferences Among Food Pantry Clients

Abstract: Introduction Food pantries serve households in need, including many with a family member with a diet-related chronic disease, yet data on client priorities to inform hunger relief practices are lacking. We used a statewide client survey in Minnesota to determine needs and priorities of food pantry clients in 2017 and 2019 and to identify how well Minnesota pantries met those needs in 2019. Methods Our survey was administered in 2017 and 2019. Food pantries in Minnesota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
1
23
1
Order By: Relevance
“…This network provides food for millions of low-income households each year, playing an important role in supporting household food security. Because many households experience food insecurity chronically, the charitable food system has become a regular source of food that contributes substantially to the overall dietary intake of individuals living in these households [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This network provides food for millions of low-income households each year, playing an important role in supporting household food security. Because many households experience food insecurity chronically, the charitable food system has become a regular source of food that contributes substantially to the overall dietary intake of individuals living in these households [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…HPP pantries generally viewed HPP as aligned with common organizational goals of supporting the health of clients without compromising their ability to choose. The ability to make choices is one of the most important pantry factors identified by clients [5]. The behavioral strategies used in HPP likely promoted buy-in among client-choice pantries since maintaining choice was one of highest priorities of these pantries.…”
Section: Discussionmentioning
confidence: 99%
“…Although some pantries are making efforts to stock healthier foods, groceries offered at food pantries often lack the nutritional value necessary to support healthy diets [4]. Prior surveys have demonstrated that clients consider healthy foods as one of the most important pantry priorities [5,6]. Evidence-based strategies to change the nutritional quality of available foods and promote selection of healthier foods by food pantry clients are important tools to mitigate adverse health outcomes in food-insecure households.…”
Section: Introductionmentioning
confidence: 99%
“…Those who visit food pantries—referred to as clients in much of the previous research literature [ 7 , 17 , 18 , 19 , 20 , 21 , 22 ], but also called neighbors or guests [ 23 ]—often visit food pantries frequently over a long period of time [ 17 , 18 , 24 , 25 ]. As a result, food from pantries may comprise a substantial portion of the total food for a household experiencing food insecurity [ 26 ]. In Minnesota, a statewide survey of food pantry clients indicated that the majority received half or more of their total food from the food pantry; visited the pantry at least monthly; and had been visiting for a year or more [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, food from pantries may comprise a substantial portion of the total food for a household experiencing food insecurity [ 26 ]. In Minnesota, a statewide survey of food pantry clients indicated that the majority received half or more of their total food from the food pantry; visited the pantry at least monthly; and had been visiting for a year or more [ 26 ]. Growing evidence suggests that among those who rely on food pantries, food obtained at the food pantry has a higher nutritional quality than food from other sources [ 24 , 25 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%